A dual SILAC proteomic labeling strategy for quantifying constitutive and cell-cell induced protein secretion - Stieß, Michael; Wegehingel, Sabine; Nguyen, Chuong; Nickel, Walter; Bradke, Frank; Cambridge, Sidney (Journal of proteome research, 2015)
Recent evidence suggests that the extracellular protein milieu is much more complex than previously assumed as various secretome analyses from different cell types described the release of hundreds to thousands of proteins. The extracellular function of many of these proteins has yet to be determined particularly in the context of three-dimensional tissues with abundant cell-cell contacts. Toward this goal, we developed a strategy of dual SILAC labeling astrocytic cultures for in silico exclusion of unlabeled proteins from serum or neurons used for stimulation. For constitutive secretion, this strategy allowed the precise quantification of the extra-to-intracellular protein ratio of more than 2000 identified proteins. Ratios covered 4 orders of magnitude indicating that the intracellular vs extracellular contributions of different proteins can be variable. Functionally, the secretome of labeled forebrain astrocytic cultures specifically changed within hours after adding unlabeled, “physiological” forebrain neurons. “Nonphysiological” cerebellar hindbrain neurons, however, elicited a different, highly repulsive secretory response. Our data also suggest a significant association of constitutive secretion with the classical secretion pathway and regulated secretion with unconventional pathways. We conclude that quantitative proteomics can help to elucidate general principles of cellular secretion and provide functional insight into the abundant extracellular presence of proteins.
Gesehen am 23.06.2020